Low-temperature degradation (LTD) behaviour of CuO-Doped tetragonal zirconia ceramic - Ramesh, Singh; Purbolaksono, J.; Hamdi, M.; Sopyan, I.; Tolouei, R.; Amiriyan, M.; Tarlochan, F.; Teng, W.D. (2012)
In the present work, the low-temperature degradation (LTD) behavior of undoped and copper oxide (CuO) doped yttria-tetragonal zirconia polycrystals ceramics sintered at 1300 degrees C was investigated. The zirconia samples were tested in three different media i.e. superheated steam at 180 degrees C/10 bar refluxing conditions in 20 hydrochloric solution at 110 degrees C and in hot air at 180 degrees C to determine the effect of hydroxyl content in triggering the tetragonal to monoclinic phase transformation. The study found that the additions of CuO significantly reduced the rate of LTD phase transformation in all media tested. The undoped zirconia exhibited severe LTD when exposed to media containing 100 hydroxyl content. Although the CuO-doped samples were generally found to have better LTD characteristics, cross-sections of aged specimens (after 200 hours of exposure in superheated steam) revealed that very thin measurable monoclinic layers were developed. The presence of hydroxyl in the test media was found to have played a significant role in controlling the LTD of zirconia ceramics.